2014
DOI: 10.1371/journal.pone.0105827
|View full text |Cite|
|
Sign up to set email alerts
|

Increase in Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) Had a Strong Impact on the Development of Type 2 Diabetes in Japanese Individuals with Impaired Insulin Secretion: The Saku Study

Abstract: Our aim was to assess the impact of increase in homeostasis model assessment of insulin resistance (HOMA-IR) on the development of type 2 diabetes in Japanese individuals with impaired insulin secretion (IIS). This study included 2,209 participants aged 30–69 without diabetes at baseline who underwent comprehensive medical check-ups between April 2006 and March 2007 at Saku Central Hospital. Participants were classified into eight groups according to the combination of baseline IIS status (non-IIS and IIS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 29 publications
3
23
0
3
Order By: Relevance
“…The HOMA-IR was used to determine IR on the basis of fasted insulin and glucose levels. Elevated HOMA-IR has a positive impact on the development of type 2 diabetes in patients with impaired insulin secretion (24). In the present study, it was demonstrated that Apelin-13 significantly reduced the elevated FPG, FINS and HOMA-IR.…”
Section: Discussionsupporting
confidence: 62%
“…The HOMA-IR was used to determine IR on the basis of fasted insulin and glucose levels. Elevated HOMA-IR has a positive impact on the development of type 2 diabetes in patients with impaired insulin secretion (24). In the present study, it was demonstrated that Apelin-13 significantly reduced the elevated FPG, FINS and HOMA-IR.…”
Section: Discussionsupporting
confidence: 62%
“…As HOMA index is usually used to calculate insulin resistance in subjects with the metabolic syndrome without diabetes, or in those with diabetes without therapy, the use of HOMA-IR may be debatable in diabetic individuals. However, many studies (30)(31)(32)(33) have also demonstrated that HOMA-IR is significantly associated with diabetes.…”
Section: Limitationsmentioning
confidence: 99%
“…The HOMA‐IR, the method for estimating the insulin resistance, has been commonly used in diabetes research for decades, and an increase of HOMA‐IR is intensely associated to the development of type 2 diabetes (Morimoto et al , ). Our experiment proved that the induction of type 2 diabetes caused by the elevation of HOMA‐IR, indicating the improvement of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%